2012
DOI: 10.1038/nmat3502
|View full text |Cite
|
Sign up to set email alerts
|

Hot exciton dissociation in polymer solar cells

Abstract: The standard picture of photovoltaic conversion in all-organic bulk heterojunction solar cells predicts that the initial excitation dissociates at the donor/acceptor interface after thermalization. Accordingly, on above-gap excitation, the excess photon energy is quickly lost by internal dissipation. Here we directly target the interfacial physics of an efficient low-bandgap polymer/PC(60)BM system. Exciton splitting occurs within the first 50 fs, creating both interfacial charge transfer states (CTSs) and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
728
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 612 publications
(788 citation statements)
references
References 33 publications
42
728
4
Order By: Relevance
“…26,28 There has been a lot of recent discussion that ultrafast CS in polymer:fullerene blends might compete with relaxation and occur from hot, highly delocalized states. 8,9,42,43 Our results are not in contradiction with such a mechanism, but further discussion is beyond the scope of the present manuscript.…”
Section: Resultsmentioning
confidence: 43%
“…26,28 There has been a lot of recent discussion that ultrafast CS in polymer:fullerene blends might compete with relaxation and occur from hot, highly delocalized states. 8,9,42,43 Our results are not in contradiction with such a mechanism, but further discussion is beyond the scope of the present manuscript.…”
Section: Resultsmentioning
confidence: 43%
“…Such non-thermalized 'hot exciton' states have been implicated recently as important precursors in the generation of photocurrent in organic photovoltaics since they undergo fission within the first 50 fs following excitation, creating both interfacial charge-transfer states and polaron species in low bandgap polymer systems 6,7 . In essence, as the energy offset between donor and acceptor materials is increased, an increasing density of long-range charge-transfer states (that is, polarons) becomes isoenergetic with the photoexcited excitonic state.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed mechanistic understanding of primary charge generation dynamics is of key fundamental importance in the development of organic solar cells, and we propose it to be generally important in photoinduced charge-transfer processes in condensed matter. Recent spectroscopic measurements on organic photovoltaic systems have reported that charged photo excitations can be generated on r100-fs time scales [2][3][4][5][6][7][8][9][10] ; however, full charge separation to produce photocarriers is expected to be energetically expensive given strong Coulombic barriers due to the low dielectric constant in molecular semiconductors. Nonetheless, experiments by Gélinas et al 11 in which Starkeffect signatures in transient absorption spectra were analysed to probe the local electric field as charge separation proceeds, indicate that electrons and holes separate by B40 Å over the first 100 fs and evolve further on picosecond time scales to produce unbound charge pairs.…”
mentioning
confidence: 99%
“…Recently, Grancini et al observed the generation of free charge carries within 50 fs for the PCPDTBT:PC60BM device using sub-20 fs pumpprobe spectroscopy. 63 From these recent spectroscopic measurements, e.g. the work by …”
Section: Ultrafast Generation Of Free Charge Carriersmentioning
confidence: 99%
“…Indeed, based on the TA measurements it has been suggested that free carriers could be generated in the range of 50 fs. 63 In the hot CT state theory, once relaxed to the ground CT states, the polaron pairs will primarily recombine as they do not have enough driving force to overcome the Coulombic attraction between each other under normal device operation conditions.…”
Section: Dissociation Via the Hot Ct Statementioning
confidence: 99%